Lithuanians and Ukrainians living in exile: traces of political relations in the West - Banionis, Juozas (Genocidas ir rezistencija, 2021)
In raising the issue of Lithuania’s freedom the political diaspora of Lithuanians understood that seeking to maintain the relevance of this problem on the international plane it is important not only to further strengthen relations with other Balts of a similar fate but also to establish contacts with the emigrants of other Eastern European nations which live in dependence of the Soviet Union and by communicating with them to seek for concerted actions in the joint liberation activity. Developing relations between the Lithuanian diaspora and the Ukrainian one became one of the directions of such cooperation.The Diplomatic Service of the Republic of Lithuania followed the principle according to which close relations linking only the Baltic States were possible, excluding Belarus and Ukraine which were in the composition of the Soviet Union before World War II; this fact definitely confirmed the international recognition of the statehood of Lithuania, Latvia and Estonia. However, taking into consideration the emerging movement of the United States of Europe whose germs dated back to the period before World War II, and which promoted the idea of uniting the states of Eastern and Western Europe, including also Ukraine, the principles which were becoming predominant changed.Supporting the idea of unification, the Ukrainian side, at the beginning offered to apply this model in Eastern Europe, which, seeking to achieve liberation should strive for unity, come together and play an active part beginning with a smaller nucleus. The block formed on the basis of the region (the Black Sea and the Baltic Sea) was seen in which, apart from Ukraine, there should be Belarus (often referred to as Belorussia), Lithuania, Latvia and Estonia, and Poland – as an ally of the block.Therefore, approving of nonrecognition of Lithuania’s and other Baltic countries’ joining the USSR, it became important to support liberation of other nations under Soviet domination, including that of Ukrainians. Main factors of the Lithuanian diaspora – the Supreme Committee for the Liberation of Lithuania or VLIK, the Lithuanian Freedom Committee (LLK), and later (from the 1960s) the Lithuanian World Community, in cooperation with the Lithuanian American Community – became engaged in a search for political relations with the Ukrainians who did not deny historical links and supported the idea of liberation. They expressed the expectations of their Motherland – Ukraine – in the West through the following organisations: the Ukrainian National Council (UNR), the Ukrainians World Congress, the Ukrainian American Congress. Raising the issue of independence of Vilnius and Lvov brough the positions of both the Lithuanian and Ukrainian diasporas closer together. Hence, it can be stated that since the end of the 1940s, Lithuanian political factors, in establishing contacts with the above-mentioned Ukrainian leaders in the West, spoke for promoting cooperation between themselves in the context of Eastern Europe. The course of the process itself was planned until full independence of Lithuania and Ukraine had been achieved, and after freedom for the nations had been regained, it was assured that cooperation would not be withheld and their historical friendship, which had become a tradition, would continue: cultural, political links would further be developed and strengthened and relations between both states would be fostered in the spirit of partnership that had been formed. It is very important that both Lithuania’s and Ukraine’s aspirations towards emancipation from the iron grip of Communism were professed while the diasporas of both nations conducted public anti-Soviet campaigns in the West.The Helsinki process that started in 1975 provided the movement of liberation of Eastern European nations, including Lithuanians and Ukrainians, with the new impetus. New forces that joined the movement did their utmost to strengthen relations between both nations and the dissidents who arrived in the West expanded their cooperation underlying the importance of a unified fight against the communist regime. At the same time the expectations and conviction of the Eastern European nations that Western democracy could be the best example of governance to that part of the old Continent were expressed.
Keywords: Lithuania; Ukraine; emigree; antisoviet resistance